Pengaruh Kompetensi Profesional Dan Kompetensi Pedagogik Terhadap Kinerja Guru Ekonomi SMA Negeri Di Kota Bandung - Raden Roro Suci Nurdianti (JURNAL ILMIAH MANAJEMEN & BISNIS, 2017)
This study aims to analyze the influence of professional competency and pedagogical economic performance of teachers  in high schools of Bandung City. The population in this research is economic teachers in public senior high schools of Bandung City. Methods that were used in this research is the explanatory survey methods, while the sample collection was undertaken through a method of simple random sampling , so we get  90 economic teachers  as a sample. Data collected from primary and secondary data through information from the school .The results of the study show professional competency and pedagogical significantly influences the performance of economic teachers in high schools in the city of Bandung.